A guide to microRNA‐mediated gene silencing. (8th October 2018) - Quévillon Huberdeau, Miguel; Simard, Martin J.
Abstract : As an important regulator of gene expression in eukaryotes, microRNAs (miRNAs) have been subject to extensive research to understand their pleiotropic roles in development and pathological processes. Here, we review strategies that have been developed to map microRNA‐target interactions and the most effective methods to attribute post‐transcriptional gene regulation through miRNA‐mediated silencing. We further discuss the importance of the biological context for silencing. Abstract : The tiny ribonucleic acid (RNA) molecules called microRNAs play an essential role in the maintenance of cells as demonstrated by several studies focusing on a plethora of human diseases. In this review, we discuss about strategies used to identify the molecular targets of those RNA molecules as well as describe the importance of studying their roles in their natural biological context.